2013
DOI: 10.1134/s1063772913020066
|View full text |Cite
|
Sign up to set email alerts
|

Class I methanol masers in low-mass star-forming regions

Abstract: Abstract. Four Class I maser sources were detected at 44, 84, and 95 GHz toward chemically rich outflows in the regions of low-mass star formation NGC 1333I4A, NGC 1333I2A, HH25, and L1157. One more maser was found at 36 GHz toward a similar outflow, NGC 2023. Flux densities of the newly detected masers are no more than 18 Jy, being much lower than those of strong masers in regions of high-mass star formation. The brightness temperatures of the strongest peaks in NGC 1333I4A, HH25, and L1157 at 44 GHz are high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Their work concluded that the brightest collisionally pumped Class I methanol masers are expected at the transitions at 36.169 GHz (4 −1 − 3 0 E) and 44.070 GHz (7 0 − 6 1 A + ), with slightly weaker masers for the 84.521 GHz (5 −1 − 4 0 E) and 95.169 GHz (8 0 − 7 1 A + ) transitions. These four transitions have been observed associated with outflows in SFRs (e.g., Kurtz et al 2004;Fish et al 2011;Fontani et al 2010;Kalenskii et al 2013). In SNRs, the 84 GHz line has not yet been reported, but the 36 GHz, 44 GHz, and 95 GHz lines have all been detected (Yusef-Zadeh et al 2008;Sjouwerman et al 2010;Pihlström et al 2011a;Shulga et al 2012).…”
Section: Model Parametersmentioning
confidence: 90%
See 1 more Smart Citation
“…Their work concluded that the brightest collisionally pumped Class I methanol masers are expected at the transitions at 36.169 GHz (4 −1 − 3 0 E) and 44.070 GHz (7 0 − 6 1 A + ), with slightly weaker masers for the 84.521 GHz (5 −1 − 4 0 E) and 95.169 GHz (8 0 − 7 1 A + ) transitions. These four transitions have been observed associated with outflows in SFRs (e.g., Kurtz et al 2004;Fish et al 2011;Fontani et al 2010;Kalenskii et al 2013). In SNRs, the 84 GHz line has not yet been reported, but the 36 GHz, 44 GHz, and 95 GHz lines have all been detected (Yusef-Zadeh et al 2008;Sjouwerman et al 2010;Pihlström et al 2011a;Shulga et al 2012).…”
Section: Model Parametersmentioning
confidence: 90%
“…Although 84 GHz and 95 GHz methanol masers have been detected in SFRs (e.g., Plambeck & Menten 1990;Kalenskii et al 2013), there are less details available for estimates of the density and temperature for these transitions (Cragg et al 1992). The results presented here show that these transitions may be found under the same range of conditions as the 36 GHz and 44 GHz lines.…”
Section: Comparison To Methanol In Sfrsmentioning
confidence: 99%
“…1. The main LMMI properties are discussed in Kalenskii et al (2013). They can be summarised as follows:…”
Section: Lmmi Propertiesmentioning
confidence: 99%
“…Plambeck & Menten 1990, Kurtz et al 2004, Cyganowski et al 2009, Voronkov et al 2014. More recently, Kalenskii et al (2013) detected Class I CH 3 OH masers (at 44, 84, and 95 GHz) towards outflows in low-mass star-forming regions, and found that Class I maser luminosities scaled with the luminosity of the driving protostar. The Class I maser series extend into the (sub)millimeter regime (e.g.…”
Section: Introductionmentioning
confidence: 97%